The endoplasmic reticulum plays a key role in α-cell intracellular Ca2+ dynamics and glucose-regulated glucagon secretion in mouse islets - Acreman, S; Ma, J; Denwood, G; Gao, R; Tarasov, A; Rorsman, P; Zhang, Q (Cell Press, 2024)
Glucagon is secreted by pancreatic α-cells to counteract hypoglycaemia. How glucose regulates glucagon secretion remains unclear. Here, using mouse islets, we studied the role of transmembrane and endoplasmic reticulum (ER) Ca2+ on intrinsic α-cell glucagon secretion. Blocking isradipine-sensitive L-type voltage-gated Ca2+ (Cav) channels abolished α-cell electrical activity but had little impact on its cytosolic Ca2+ oscillations or low-glucose-stimulated glucagon secretion. In contrast, depleting ER Ca2+ with cyclopiazonic acid or blocking ER Ca2+-releasing ryanodine receptors abolished α-cell glucose sensitivity and low-glucose-stimulated glucagon secretion. ER Ca2+ mobilization in α-cells is regulated by intracellular ATP and likely to be coupled to Ca2+ influx through P/Q-type Cav channels. ω-Agatoxin IVA blocked α-cell ER Ca2+ release and cell exocytosis, but had no additive effect on glucagon secretion when combined with ryanodine. We conclude that glucose regulates glucagon secretion through the control of ER Ca2+ mobilization, a mechanism that can be independent of α-cell electrical activity.